L’accento straniero degli italiani: Esiste un "accento italiano" comune? - Huszthy, Bálint (Verbum – Analecta Neolatina, 2013)
In this paper I want to present some phonetic and phonological phenomena which systematically recur in the foreign accent of Italian speakers of different origin. The aim of the paper is to argue in favour of the existence of a common “Italian foreign accent”, which may offer a new and unusual approach to the synchronic phonology of Italian. The conclusions of the research will show that the Italian accent can be determined only at the phonological level, for example through various phonological processes related to the syllabic structure of Italian.